The annual direct costs of stable COPD in Greece - Stafyla E; Geitona M; Kerenidi T; Economou A; Daniil Z; Gourgoulianis KI (International Journal of COPD, 2018)
Eirini Stafyla,1 Mary Geitona,2 Theodora Kerenidi,1 Athina Economou,3 Zoe Daniil,1 Konstantinos I Gourgoulianis1 1Respiratory Medicine Department, University of Thessaly School of Medicine, University Hospital of Larissa, Larissa, 2School of Social Sciences, University of Peloponnese, Corinth, 3Department of Economics, University of Thessaly, Volos, Greece Introduction: Chronic obstructive pulmonary disease (COPD) places a major burden on health care systems and has substantial economic effects; however, the cost of stable disease in Greece has never been thoroughly explored. The objective of the study was to estimate the annual COPD patient cost during the maintenance phase and explore the relationships between the cost and disease severity.Methods: Data were collected from 245 COPD patients (male: 231, mean age: 69.5±8.8 years) who visited the outpatient unit of University Hospital of Larissa in 2014 and 2015. Patients were classified according to Global Initiative for Chronic Obstructive Lung Disease (GOLD) guidelines, and the patients’ direct cost during the maintenance phase was calculated.Results: Eleven percent of COPD patients were stage I, 48.2% were stage II, 29% were stage III, and 11.8% were stage IV. According to the GOLD groups, 23.3% of patients were grade A, 15.5% were grade B, 22.9% were grade C, and 38.4% were grade D. The mean annual direct cost for stable disease was estimated at €1,034.55 per patient, of which €222.94 corresponded to out-of-pocket payments. The annual cost ranged from €408.23 to €2,041.89 depending on GOLD stages (I–IV) and from €550.01 to €1,480.00 depending on GOLD groups (A–D). The key cost driver was pharmaceutical treatment, which reflected almost 71% of the total expenses for the management of stable disease. The mean annual per-patient cost was two to three times higher for those with advanced disease (stages III–IV) compared to those with stages I–II disease, and it doubled for “high-risk” patients (groups C–D) compared to “low-risk” patients (groups A–B).Conclusion: The cost of COPD during the maintenance phase is remarkable, with the key cost driver found to be pharmaceutical treatment and social insurance funds the key payer for treating COPD patients in Greece. The cost of stable disease is proportional to the severity of COPD, and it is doubled in patients who belong to high-risk groups. Keywords: stable COPD, direct cost, annual cost, GOLD stages, GOLD groups, Greece